ESTILO DE APRENDIZAJE VARK Y SU INFLUENCIA EN EL RENDIMIENTO ACADEMICO DE LOS ESTUDIANTES DE LA CARRERA DE PEDAGOGIA DE LA ACTIVIDAD FÍSICA Y DEPORTE DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO, PERIODO ACADEMICO OCTUBRE 2023 - MARZO 2024 - CALDERON ANGULO JOSE ANDRES (2024)
In the analysis of learning styles in the Physical Activity and Sports Pedagogy degree using the VARK model, a significant diversity in student preferences is revealed. Four main styles are identified: visual, auditory, reading/writing and kinesthetic. The results indicate that, although some students perceive certain styles as less useful, there is considerable variability in the application of specific tools associated with each style. Regarding the recommendations, a more flexible pedagogical adaptation is suggested to meet different preferences. For visual learners, experiences can be enhanced through the use of artwork, mind maps, and visual presentations. Hearing learners can benefit from group learning strategies, class recordings, and oral explanations. For readers/writers, note taking, written summaries, and participating in forums are useful strategies. For kinesthetics, the implementation of active tests, direct feedback and self-assessment is recommended. This analysis highlights the complexity and variability of learning style preferences among Physical Activity and Sports Pedagogy students. The application of inclusive pedagogical strategies, considering the specific tools associated with each style, is presented as essential to improve the learning experience and optimize academic performance.